DETERMINATION OF COMPETENCIES NEEDED BY BUSINESS EDUCATION GRADUATES FOR ENTREPRENEURIAL SUCCESS IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The need to ensure adequate preparation of business education graduates for selfemployment necessitated this study. The study was to determine the entrepreneurialcompetencies needed by business education graduates for entrepreneurial success inAnambra state. The study considered 237 business education graduates working inAnambra State. Tworesearchquestions guided the study and two hypotheseswere tested at0.05 level of significance. Survey research design was adopted for the study. Data werecollected using a 47 item questionnaire validated by three experts from the Faculty ofEducation, Nnamdi Azikiwe University, Awka. The test re-test reliability method and thePearson Product Moment Coefficient were used to obtain the overall reliability coefficientof 0.85. The data collected using the questionnaire were analysed using mean values toanswer the research questions while the null hypotheses were tested at 0.05 level ofsignificance using z-test and ANOVA. The findings revealed that business educationgraduates need conceptual, organizing, strategic and human relation competencies forentrepreneurial success. It also revealed that respondents' gender, qualifications andworking experience did not affect their mean ratings on conceptual, strategic and humanrelation competencies but type of institution significantly affected their mean ratings onorganizing competencies. It was recommended among others that tertiary institutionsshould encourage business education lecturers and students to organize workshops andconferences with a view to keeping them abreast of contemporary issues and needs ofthebusiness world and world of work.
Keywords: Competencies, entrepreneurial success, business education graduates, tertiary institutions